Estudo da estruturacromossômica de Astyanax bockmanni (Teleostei, Characiformes) em diferentes populações: enfoque em cromossomos B - Daniel, Sandro Natal [UNESP] (2014)
Among the fish of the Neotropical region, we have the Characidae family whose genus Astyanax is the most common and diverse, with 141 species validated. Studies with several species of the group have shown a particular population dynamics, leading to the formation of genetically variable populations, besides the occurrence of B chromosomes, which in this genus exhibit intense polymorphisms. These chromosomes are classified as additional elements dispensable, and are present in plants, fungi and animals of varying frequencies and morphologies. So, six distinct populations of Astyanax bockmanni collected in the basins of the Tietê and Paranapanema were analyzed, beyond samples of the species A. fasciatus and A. paranae carriers of supernumerary chromosomes. The studies were based on classical cytogenetic techniques (Giemsa staining, impregnation with silver nitrate, and C-banding), and molecular (fluorescence in situ hybridization FISH and animal by means of 18S and 5S rRNA probes; genes for histones H1, H3, and transposable elements Rex1, Rex3 and Rex6). We also performed microdissection, amplification, marking and hybridization of a B-specific probe acrocentric B chromosome of A. bockmanni, named Babock. The results indicated that all specimens of A. bockmanni and A. paranae presented 2n=50 chromosomes. A. fasciatus showed 2n=46 chromosomes default. All karyotypes of the three species were made up of chromosomes metacentric, submetacentric, subtelocentric and acrocentric types. The species A. bockmanni (Alambari population) were observed B microchromosomes metacentric and acro Supernumerary, were acro and subtelocentric observed in the species A. fasciatus, and the metacentric B chromosomes in type A. paranae. The six populations of A. bockmanni showed differences in the constitutive heterochromatin and multiple NOR except the population Capivara river, which indicated a simple NOR system. Additionally, the 18S rRNA gene revealed ...